External drivers of heavy metal bioavailability and probabilistic ecological risk in water-level-fluctuating wetlands - Huan Zeng; Mingjun Ding; Hua Zhang; Yuping Wu; Xiang Xu; Honmei Chen; Liyao Chen; Yinhui Jiang; Peng Wang; Gaoxiang Huang (Ecological Indicators)
Water-level-fluctuating wetlands are areas rich in biodiversity and are major repositories for heavy metal enrichment. In this study, we investigated soil/sediment heavy metals (Co, Ni, Cu, Zn, Cd, and Pb) and their bioavailability in three landscape belts (mudflat belt, Carex cinerascens belt, and Triarrhenalu⁃tarioriparia belt), and evaluated the probabilistic ecological risk of heavy metals. The results showed that the total heavy metal content in the soil significantly increased from land to lake. Conversely, the bioavailability of heavy metals decreased significantly. Vegetation promoted heavy metal bioavailability and Cd had the highest relative bioavailability (5.65E-4) in water-level-fluctuating wetlands. The total Fe content was identified as the primary mutual factor influencing heavy metal enrichment, whereas the total contents of Cu and Cd significantly affected the bioavailability of six heavy metals. The random forest results indicated that total Cu and Cd contents were also the primary contributors to their own bioavailability. However, the relationship between the total content of Cd and Cu and their bioavailability was not linear and changed significantly before and after the threshold (46.98 mg·kg−1 for Cu, 0.903 mg·kg−1 for Cd). The responses of Cd bioavailability to the total Cd content before and after the threshold exhibited opposite results, and there was great potential for enhancing Cd bioavailability in water-level-fluctuating wetlands. Cu bioavailability before and after the threshold value increased significantly as the total Cu content increased, and only the rate after the threshold value reduced. The probabilistic ecological risk of individual heavy metals was ordered as follows: Cu (9.63 %) > Zn (9.42 %) > Cd (4.43 %) > Co (0.578 %) > Pb (0.307 %) > Ni (0.210 %). The combined probabilistic ecological risk (1.72E-15) was low. The result is crucial for understanding the fate mechanism of heavy metal and provide scientific insights for controlling heavy metal pollution in typical wetland.